Emotional competence profile of nursing students in clinical practice - Mendes, Carina Maria Pires (2024)
Analyze the Emotional Competence (EC) profile in nursing students in clinical practice of learning. Methods: A quantitative, descriptive, cross-sectional and correlational study was carried out through Emotional Competence Veiga Scale (ECVS), responses, applied to a 103 nursing students sample, mostly female, and aged between 19 and 44 attending a nursing degree coursean a north-east of Portugal institution. This data collection instrument, presents the CE 5 dimensions of the construct, operationalized along 112 items: each one is an independent variable representing an attitude or behavior operationalized through a Likert Scale with 7 cells: 1 (never), 2 (rarely), 3 (infrequent), 4 (normally), 5 (frequently), 6 (very frequently) and 7 (always), with the cutoff point at 4. The data was subjected to statistical analysis in SPSS allowing the EC profile. Results: The 5 dimensions emerge in the score of EC “normally”, but self-awareness emerges with the highest score, X=4.93 (dp=0.791), followed by Empathy with X= 4.84 (dp=1.02), and Self-motivation X= 4.70 (dp=0.687), Group Emotion Management with X= 4.61 (dp=1.05) and, with the lowest value, Emotion Management with X= 4.29 (dp=0.670), respectively. The global sample shows a moderate level in EC, but with low score in Self emotions management, and without any dimension reaching frequent or very frequent.